Pitting corrosion behavior of a laser hardened, high-alloyed steel. (February 2019) - Mehner, T; Landgraf, P; Haack, E; Scharf, I; Grund, T; Lampke, T
Abstract: Laser hardening provides significant advantages in processing time, and energy consumption compared to conventional hardening processes, especially for small batches. In addition, the functional characteristics can be adjusted locally for different applications. However, the differences of the microstructural states in the laser-treated areas and the surrounding untreated base material may result in corrosion issues. In this paper, the corrosion behavior of the high-alloyed, laser-treated steel X153CrMoV12 (1.2379) used in the meat-processing industry is investigated in Hanks' balanced salt solution, a simulated body fluid, globally by immersion tests and locally by microelectrochemical investigations, depending on the measured temperature in the laser spot. Differences of the susceptibility to pitting, as well as correlation to thermodynamic calculations were found. Thus, the application-related corrosion behavior can be estimated numerically.